Continuous thermosalinograph oceanography along RV Maria S. Merian cruise MSM99/2 - Christopher Schmidt; Michael Schlundt (PANGAEA, 2021)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems. Usually, the systems are changed after 6 hours. While temperature is taken at the water inlet in about 6.5 m depth, salinity is estimated within the interior measurement container from conductivity and interior temperature. Salinity was calibrated independently for both measurement containers (MCs). No correction was done for temperature. For details to all processing steps see Data Processing Report.